Characteristics of innovation: a customer-centric view of barriers to the adoption of a renewable energy system. (16th February 2009) - Tapaninen, Aija; Seppanen, Marko; Makinen, Saku
Annually, billions of Euros are spent globally on developing a range of green technologies, including bio-heating technologies, as part of a push into the renewable energy market. This paper considers customer perceived barriers to the adoption of wood pellet heating technology. Theoretically, the paper is based on diffusion and innovation decision theory and utilises two different theoretical frameworks: 'perceived characteristics' and 'basis of competition'. Customers' perceived barriers were collected through a survey (sample size N = 154) of Finnish housing expo attendance in 2007. The innovation adoption of wood pellet heating systems was observed to be at the rather early stages in Finland. The results somewhat contradict theoretical expectations concerning evolution of the basis of competition. The results also indicate that while other perceived characteristics were present, trialability and observability were not found in our analysis. Lacking the trial is usually typical of long-commitment investments such as bio energy systems.